The Cambridge history of science. Volume 2, Medieval science - Lindberg, David C.; Shank, Michael H. (Cambridge : Cambridge University Press, 2013)
This volume in the highly respected Cambridge History of Science series is devoted to the history of science in the Middle Ages from the North Atlantic to the Indus Valley. Medieval science was once universally dismissed as non-existent - and sometimes it still is. This volume reveals the diversity of goals, contexts and accomplishments in the study of nature during the Middle Ages. Organized by topic and culture, its essays by distinguished scholars offer the most comprehensive and up-to-date history of medieval science currently available. Intended to provide a balanced and inclusive treatment of the medieval world, contributors consider scientific learning and advancement in the cultures associated with the Arabic, Greek, Latin and Hebrew languages. Scientists, historians and other curious readers will all gain a new appreciation for the study of nature during an era that is often misunderstood.
Introduction / Michael H. Shank and David C. Lindberg -- Islamic Culture and the Natural Sciences / F. Jamil Ragep -- Islamic Mathematics / J.L. Berggren -- THE MIXED MATHEMATICAL SCIENCES / Elaheh Kheirandish -- Islamic Astronomy / Robert G. Morrison -- MEDICINE IN MEDIEVAL ISLAM / Emilie Savage-Smith -- Science in the Jewish Communities / Y. Tzvi Langermann -- SCIENCE IN THE BYZANTINE EMPIRE / Anne Tihon -- Schools and Universities in Medieval Latin Science / Michael H. Shank -- The Organization of Knowledge / Joan Cadden -- SCIENCE AND THE MEDIEVAL CHURCH / David C. Lindberg -- Natural Knowledge in the Early Middle Ages / Stephen C. McCluskey -- Early-Medieval Cosmology, Astronomy, and Mathematics / Bruce S. Eastwood -- EARLY-MEDIEVAL MEDICINE AND NATURAL SCIENCE / Vivian Nutton -- Translation and Transmission of Greek and Islamic Science to Latin Christendom / Charles Burnett -- THE TWELFTH-CENTURY RENAISSANCE / Charles Burnett -- MEDIEVAL ALCHEMY / William R. Newman -- Change and Motion / Walter Roy Laird -- Cosmology / Edward Grant -- Astronomy and Astrology / John North -- THE SCIENCE OF LIGHT AND COLOR, SEEING AND KNOWING / David C. Lindberg and Katherine H. Tachau -- Mathematics / A. George Molland -- Logic / E. Jennifer Ashworth -- GEOGRAPHY / David Woodward -- Medieval Natural History / Karen Meier Reeds and Tomomi Kinukawa -- ANATOMY, PHYSIOLOGY, AND MEDICAL THEORY / Danielle Jacquart -- Medical Practice / Katharine Park -- TECHNOLOGY AND SCIENCE / George Ovitt.
Title from publisher's bibliographic system (viewed on 15 Jan 2016).
Keywords: Science, Medieval; Science -- History